Climate Changed Effect on Irrigated Water Supply at Segaran Malang, Indonesia - Limantara, Lily Montarcih; Djunaedi, Djunaedi; Ibrahim, Mochammad (Fakultas Teknik, Universitas Brawijaya, 2010)
This paper studied the effect of climate change to optimization of irrigated water supply atSegaran Irrigation Area. Global climate exchange caused some effects to hydrological factorssuch as temperature, humidity, seasonal time exchange and the quantity of rainfall. These exchanges would give contribution exchange to the operation of water irrigation. The methodology consisted of optimization irrigated water supply with Simplex Linear Programmingfor two time series such as before and after climate exchange. Results can use as the pattern of allocating water supply at Segaran irrigation area, due to the effect of climate exchange. Global climate exchange did not cause irrigated water supply and crop intensity.Key words: climate exchange, irrigation water, linear programming